Queer Hispanic Men and Their Perceptions of Servingness at Hispanic-Serving Institutions - Andrew S. Herridge (Social Sciences)
Institutional diversity and support for queer Hispanic men is an important component of postsecondary education. While some postsecondary institutions have worked to become more inclusive, queer students continue to experience harassment and discrimination. Guided by the Unifying Model of Sexual Identity Development, the Model of Multiple Dimensions of Identity, and concepts of servingness, this study explored the perceptions of queer Hispanic men on whether HSIs serve their needs based on the intersecting identities they hold. Strategies for rethinking the HSI designation and developing intentional programs and policies to support both queer Hispanic students at Hispanic-serving institutions are presented.